Transformasi Third Place Berbasis Learning Commons: Analisis Pemanfaatan Library-Cafe di Universitas Muhammadiyah Surakarta - Asri Tata; Imam Mahmudi (Jurnal Gema Pustakawan, 2025)
This study aims to describe the utilization of the Library-Cafe service at the Universitas Muhammadiyah Surakarta (UMS) Library as a supporting facility for students’ learning activities. The Library-Cafe was established as a transformation of the "third place" to improve library service quality and fulfill higher education library accreditation standards. This research employed a descriptive qualitative method, with data collected through in-depth interviews with managing librarians, direct observations, and facility documentation. The results indicate that the Library-Cafe is implemented through two distinct service models: a self-service dry canteen located inside the library building to support student needs during night study sessions, and a wet canteen outside the building providing heavy meals during daytime operational hours. Student responses toward this service are highly positive, offering spatial accessibility, flexibility, and convenience during academic activities. The main challenges identified include limited human resources for supervision, cleanliness management issues, and operational budget constraints. Strategic solutions formulated include optimizing the role of Library Ambassadors, integrating simple transaction technologies, and strengthening partnerships with campus internal business units. Overall, the Library-Cafe contributes significantly to transforming the library into a productive and adaptive learning commons.